58. Clinical efficacy of short-lasting ketogenic diet in migraine might be due to a general normalization of cortical hyperresponsivity rather than to a direct modulation of the brainstem activity. Issue 12 (December 2017) - Di Lorenzo, C.; Coppola, G.; Bracaglia, M.; Bove, I.; Di Lenola, D.; Serrao, M.; Parisi, V.; Pierelli, F.
Abstract : We previously reported that a short-lasting period of ketogenic diet (KD) regimen can help to prevent migraine and can normalize its interictally abnormal cortical hyperresponsivity. Here, we aimed to verify whether cerebral cortex is the primary site of KD-related changes or if the latter are the expression of ketones ability to modulate brainstem subcortical structures. We simultaneously recorded the nociceptive specific blink (nBR, a marker of the brainstem trigeminal activity) and cortical pain-related evoked potentials (PREP) elicited by the stimulation of right the supraorbital division of the trigeminal nerve in 18 migraine without aura patients before and after 1-month of KD, during ketogenesis. We measured nBR R2 component as well as PREP amplitude habituations over 2 blocks of 5 averaged responses. We confirmed the ability of 1-month KD of significantly decreasing mean attack frequency and duration. KD significantly induced normalization of the interictally reduced PREP habituation (pre: +1.8, post: −9.1), while nBR habituation remained unchanged. Here, we provided evidence that the clinical efficacy of a short-lasting KD regimen in migraine can be principally due to a general normalization of the interictal cortical dysfunction, and not to a direct modulation of the subcortical brainstem activation.